TRACTOR GEARBOX: RESEARCH OF SHIFTING GEARS’ PROCESSES - N. N. Demidov; A. A. Krasilnikov; S. I. Hoodorozhkov (Вестник СибАДИ, 2020)
Introduction. The process of shifting gears under load is one of the most complex types of dynamic process in the transmissions of transport, road and construction vehicles. Currently, the existing calculation methods do not fully reflect the features of the engine and automated gearbox interaction by switching stages under load using more than two friction clutches at the same time. The paper discusses the method of calculating the dynamic characteristics of the gearbox with the simultaneous use of both two and four friction clutches by shifting gears under load with forward and reverse switching. The authors present the results of the dynamic characteristics of the theoretical study of the automated gearbox with frictional stages’ switching under load and without breaking the power flow.Materials and methods. The main method was based on a system approach to the dynamic processes study and on the modeling of the gearbox operation together with the internal combustion engine. The authors took into account the regulatory, speed and load engine characteristics, resistive torque variation, rate of pressure rise in clutches by shifting to higher and lower gears. The paper performed theoretical modeling of processes using the MATLab package and the Simulink application. Using the main blocks of this application, the authors created models of physical components: an internal combustion engine, friction clutches, gear reducers, elastic shafts, damping devices and tractor power transmission control systems.Results. As a result, the authors obtained calculated data of the dynamic processes, variations in speed and rotational torque on the gearbox shafts; the load on the engine by shifting gears at different values of the start and finish time in switching on and off the gearbox friction controls. The paper presented the relevant graphs of the processes.Discussion and conclusions. The developed method of calculating the dynamic characteristics of the gearbox allows simulating workflows by shifting to higher and lower gears. This method takes into account both the parameters of the gearbox design and of the control actions: the rate of switching on the friction clutches; the time intervals of overlapping the “on and off” clutches. Therefore, in relation to the considered gearbox, the authors determine the values of the optimal time control commands of the friction by shifting.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.